Assessing land use deviations from spatial plans amid nickel mining expansion in Central Halmahera - Winda Hanifah; Mirza Irwansyah; Tia Adelia (Journal of Infrastructure Planning and Engineering, 2025)
The rapid expansion of industrial and nickel mining activities in Central Halmahera has driven dynamic changes in land use, often leading to conflicts with established spatial plans. This study identifies land use deviations from the North Maluku Provincial Spatial Plan (2024–2043) using spatial analysis techniques. Through the overlay method, recent land use and land cover data (from 2022) were compared with the designated spatial zoning plan. The analysis results show a generally high level of compliance, with approximately 98.13% of the total 247,596.80 hectares aligning with the spatial zoning plan. However, significant deviations were found in the Mangrove Zone (17.94%) and Marine Conservation Zone (47.98%) due to settlements and infrastructure development. These changes are driven by industrial growth, a surge in the workforce, and increased demand for housing and services. The findings reveal real challenges in the effectiveness of spatial planning instruments to control land use changes. Emphasis on the need for proactive and integrated spatial governance can be addressed through stricter zoning regulation enforcement, continuous monitoring, and active community involvement in the planning process to ensure sustainable land management amid ongoing extractive industry expansion.